The Influence of the Role of the School Committee on the Implementation of School-Based Management - Jumirin Jumirin; Ngurah Ayu Nyoman Murniati; Endang Wuryandini (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the influence of the role of school committees on the implementation of school-based management (SBM) in private elementary schools in Pemalang district. The method used in this study is a descriptive method with a quantitative approach, namely research with quantitative data which is then processed and analyzed for conclusions. The first step before the research is taken is to conduct a theoretical study, then the following stages are carried out; first, compiling research instruments, secondly testing the validity and reliability of instruments, thirdly the process of data retrieval, fourth tabulation of data, data processing and interpretation of data, fifth drawing conclusions. The results showed that; first, The role of the school committee as a judge, supporter, mediator and controller of the implementation of SBM obtained a minimum score of 69 and a maximum score of 202 with a score range of 133. The data can be described as saying that out of 100 respondents who stated that the role of the school committee was good, 13 people were equivalent to 13%, stated that 37 people played a good role. 37%, stated that 39 people played a role equivalent to 3 9% stated that they played less role as many as 9 people equivalent to 9% and respondents who stated that they did not play a role as many as 2 people were equivalent to 2%. With a mean value of 149.27 and a mode value of 162, the value is included in the interval class 150 – 176 in the good/high category. The conclusion of this study is that the level of SBM implementation in Pemalang District Private Primary School is influenced by the level of role of the school committee. The higher the role of the school committee, the more the implementation of SBM will increase. Similarly, if the role of the school committee is low or lacks a role, then the level of implementation of SBM will also decrease.